From Toxicity to Selectivity: Coculture of the Fluorescent Tumor and Non-Tumor Lung Cells and High-Throughput Screening of Anticancer Compounds - Skvortsov, D.A.; Kalinina, M.A.; Zhirkina, I.V.; Vasilyeva, L.A.; Ivanenkov, Y.A.; Sergiev, P.V.; Dontsova, O.A. (Frontiers in Pharmacology, 2021)
For the search of anticancer compounds in modern large chemical libraries new approaches are of great importance. Co-cultivation of the cells of tumor and non-tumor etiology may reveal specific action of chemicals on cancer cells and also take into account some effects of tumor cells’ microenvironment. Fluorescent Cells Co-cultivation Test (FCCT) has been developed for screening of substances that are selectively cytotoxic on cancerous cells. It is based on mixed culture of lung carcinoma cells A549_EGFP and noncancerous fibroblasts of lung VA13_Kat, expressing different fluorescent proteins. Analysis of the cells was done with the high-resolution scanner to increase detection rate. Combination of co-cultivation of cells with scanning of fluorescence reduces the experimental protocol to three steps: cells seeding, addition of the substance, and signal detection. The FCCT analysis does not disturb the cells and is compatible with other cell-targeted assays. The suggested method has been adapted for a high-throughput format and applied for screening of 2491 compounds. Two 4-hydroxyquinazoline derivatives were unraveled to be reproducibly selective in FCCT though were invisible in MTT test with cytotoxicity measurement in individual lines. Six structurally diverse indole, coumarin, sulfonylthiazol and rifampicin derivatives were found and confirmed with independent assay (MTT) to be selectively cytotoxic to cancer cells in the studied model.